Conversion of carbon dioxide to methanol over visible light responsive catalyst - Mariotte, Patrick Jebi (2017)
The significant increase of carbon dioxide contributed for the largest share of the world’s greenhouse gas emissions. There is a growing need to mitigate CO2 emissions. One of the strategies to mitigate CO2 emissions is using CO2 as a raw material in chemical processes. In the present study, a TiO2 loaded copper (II) oxide (CuO) photoelectrode was synthesized, characterized and studied for photoelectrocatalytic (PEC) reduction of carbon dioxide (CO2) into methanol under visible light (λ > 470 nm) irradiation. In this perspective, The material was constructed via sol-gel method from copper (II) nitrate, Cu(NO3)2.3H2O (99 %) and commercial Degussa P25 TiO2 as precursors. The photocatalysts were characterized by X-ray diffraction, UV-vis absorption specra, X-ray photoelectron spectroscopy (XPS), photoluminescence spectrophotometer, and mott schottky (MS). Linear sweep voltammetry (LSV) was employed to evaluate the effect of visible light (λ >400 nm) on the CO2 reduction reactions. The characterization results indicated that the band gap energy of the CuO-TiO2 catalyst from UV-Vis is 1.39 eV. The flat band potential calculated from the MS data as 0.83 V versus normal hydrogen electrode (NHE). The LSV the dark and under visible light irradiation further support the visible light-responsive photocatalytic activities CuO-TiO2 giving onset potential value from -0.20 V with current peak potential appearing at -0.35V (vs NHE) suggesting an increase in photocurrent and occurrence CO2 photoreduction reaction. The PEC performance of CuO-TiO2 photocatalyst showed an increased methanol yield of 20.1 μmol.L-1.cm-2 under visible light irradiation.